Notifications Efficiency, Impact, and Interference in Second-Screen Scenarios. Issue 12 (1st December 2016) - Abreu, Jorge; Almeida, Pedro; Silva, Telmo; Aresta, Mónica
ABSTRACT: The growing use of second-screen devices stresses the importance of finding a balance between engagement, distraction, and disturbance of its users, while simultaneously watching television. In this framework, this article reports on a study designed to analyze the efficiency, impact, and interference of different notification strategies aiming to identify the best approach to be used when an alert is needed in second-screen scenarios. A prototype able to deliver synchronized information related with TV content, with intervals of 10, 30 and 60 s, followed by individual or combined notifications (e.g., audio, visual, and haptic—on the tablet and visual—on the TV) was developed. A laboratory adapted to replicate a living room was set up and a test that involved watching three segments of a 20-min clip while using the prototype was carried with 30 participants, under a cognitive walk-through protocol. Quantitative and qualitative results show that receiving notifications while watching TV is effective in alerting users about new information, despite its inherent cognitive disturbance for the TV viewing experience. It was also possible to highlight that in an HCI perspective, the most suitable strategy for integrating notifications (considering type and cadence) should be based on a combination of a visual notification (displayed only on the TV screen) along with a haptic notification (vibration on the tablet); spaced by an interval of at least 30 s.